Anti-Th17 and anti-Th2 responses effects of hydro-ethanolic extracts of Aframomum melegueta, Khaya senegalensis and Xylopia aethiopica in hyperreactive onchocerciasis individuals' peripheral blood mononuclear cells. - Gnatoulma Katawa; Essoham Ataba; Manuel Ritter; Oukoe Marthe Amessoudji; Essimanam Rosalie Awesso; Pélagie Edlom Tchadié; Fagdéba David Bara; Fekandine Victoire Douti; Kathrin Arndts; Tchadjobo Tchacondo; Komlan Batawila; Yaovi Ameyapoh; et al. (Public Library of Science (PLoS), 2022)
Hyperreactive onchocerciasis (HO) is characterized by a severe skin inflammation with elevated Th17-Th2 combined responses. We previously demonstrated the anthelminthic activity of Aframomum melegueta (AM), Xylopia aethiopica (XA) and Khaya senegalensis (KS) used by traditional healers to treat helminthiasis in the endemic area of Togo. However, their effect on severe onchocerciasis is poorly investigated. The present study aimed to investigate the anti-Th17 and anti-Th2 effects of hydro-ethanolic extracts of AM, XA and KS during HO. Onchocerca volvulus-infected individuals were recruited in the Central region of Togo in 2018. Isolated peripheral blood mononuclear cells (PBMCs) from both generalized onchocerciasis (GEO) and HO forms were activated with anti-CD3 and anti-CD28 monoclonal antibodies in the presence or absence of the hydro-ethanolic extracts of AM, XA and KS as well as their delipidated, deproteinized and deglycosylated fractions. After 72 hours, cytokines were assayed from cell culture supernatants. Then, flow cytometry was used to investigate the effects of the extracts on cell activation, proliferation, intracellular cytokines and T cells transcription factors. The production of both Th17 and Th2 cytokines IL-17A and IL-5 were significantly inhibited upon T-cell receptor (TCR) activation in the presence of the hydro-ethanolic extracts of AM, XA and KS in HO individuals' PBMCs in vitro. AM and XA inhibited CD4+RORC2+IL-17A+ and CD4+GATA3+IL-4+ cell populations induction. This inhibition was not Th1 nor Treg-dependent since both IFN-γ and IL-10 were also inhibited by the extracts. AM and XA did not interfere with T cell activation and proliferation for their inhibitory pathways. Lipid and protein compounds from AM and XA were associated with the inhibition of IL-17A. This study showed that in addition to their anthelminthic effects, hydro-ethanolic extracts of Aframomum melegueta, Xylopia aethiopica and Khaya senegalensis could downregulate both Th17 and Th2 responses and prevent the severe skin disorder observed.